Analisis Kadar Alkaloid Total Pada Getah Pohon Bangang (Tabernaemontana Macrocarpa Jack) Menggunakan Spektrofotometri UV-VIS - Ovita Dewi; Rahmadani Rahmadani; Tuti Alawiyah; Salwati Salwati (Indonesian Journal of Medical and Pharmaceutical Science, 2026)
Background: Bangang tree latex (Tabernaemontana macrocarpa Jack.) is a natural material empirically used by the community as traditional medicine. However, scientific data on its secondary metabolite content, particularly alkaloids, remain limited. The genus Tabernaemontana contains alkaloids with potential pharmacological activity, warranting quantitative analysis of total alkaloids in Bangang tree latex. Objective: This study aimed to identify alkaloid compounds in Bangang tree latex through phytochemical screening and determine the total alkaloid content using UV-Vis spectrophotometry. Methods: This research was a quantitative descriptive study. Fresh latex was dried, reduced in size, and extracted by maceration using 96% ethanol. Alkaloid identification was performed using Dragendorff, Mayer, and Wagner reagents. Total alkaloid content was determined using caffeine standard, BCG reagent, phosphate buffer pH 4.7, and chloroform at a maximum wavelength of 407 nm with an Operating time of 41 minutes. Results: The extract yield was 4.08%. Qualitative tests showed positive alkaloid results with all three reagents. The caffeine calibration curve produced the regression equation y = 0.003x + 0.0131 with R² = 0.9961 and r = 0.9980. The average sample absorbance of 0.036 produced a concentration of 7.633 ppm and a total alkaloid content of 76.33 mg CAE/g extract. Method validation showed %RSD of 1.74%, recovery of 99.05%, LOD of 0.730 ppm, and LOQ of 2.200 ppm. Conclusion: Bangang tree latex was positive for alkaloids, and its total alkaloid content could be determined using UV-Vis spectrophotometry.